Influence of Service Quality and Customer Satisfaction Analysis on Consumer Loyalty - Rezky Nurbakti; Bambang Supriyadi; Djoko Surahmat; Miska Irani Tarigan; Ade Perdana Siregar (Quantitative Economics and Management Studies, 2023)
The purpose of this research is to analyze the effect of service quality and customer satisfaction on customer loyalty in one of the companies engaged in the hospitality services sector in the city of Yogyakarta. The type of research used in this study uses a quantitative associative research method, namely, the research conducted aims to determine the influence or relationship between the independent variables on the dependent variable. The data source used in this study uses primary data obtained through observation and the results of questionnaire answers that have been filled out by consumers who have stayed at one of the hotels in the city of Yogyakarta with the population used in this study, namely guests who have visited and stayed with the number of samples used by 100 people. Data analysis in this study used SPSS software by conducting hypothesis testing consisting of a coefficient of determination test (R-square) and a partial t test. Based on the results of the data analysis that has been carried out in the first hypothesis (H1), which states that service quality has a positive and significant effect on consumer loyalty, the t-count value of 6,915 is greater than the t-table value, which is 1,661, testing the second hypothesis (H2), which states that customer satisfaction has a positive and significant effect on consumer loyalty, the t-count value of 6,642 is greater than the t-table value, which is 1,661. which means that service quality and customer satisfaction have a positive and significant effect on consumer loyalty, while the R-square value obtained is 0.655, which states that the variables of service quality and customer satisfaction affect consumer loyalty by 65.50%, and the remaining 34.50% is influenced by other variables.